Sistem Pengendalian Manajemen dalam Upaya Meningkatkan Kinerja Perusahaan dengan Metode Balance Scorecard - Wiratha, Andre; Kemalasari, Nur; Lubis, M. Zaky Mubarak (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study is to find out how important the Management Controlling System is in improving company performance using the Balanced Scorecard for MSMEs in Batusangkar City, West Sumatera. The type of research used is qualitative research. The data source used in this study is primary data obtained from the result of structured interviews with MSMEs actors in the service sector, namely Budi Motor Service. The result of this study indicate that the implementation of the Management Controlling System with the Balance Scorecard methodhas improved the company’s performance, Budi Motor Service is more planned in several ways, including: First, in the company’s financial perspective where bookkeeping is more structured an uses accounting principles, Second, the customer perspective where the company tries to establish relationships with customers by utilizing advance in information technology, such as social media. Third, learning and growth perspective using technology to help work processes. And Fourth, internal business process perspective, where the company development by creating business units that support the company’s main business Budi Motor Service.